A METAPHOR ANALYSIS IN KUNTO AJI'S SONG ALBUM "MANTRA MANTRA - Valensia Rossy simbolon; Erika Sinambela; Jubil Ezer Sihite (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study examines the use of metaphor in Kunto Aji’s album Mantra Mantra as a form of figurative language that conveys complex emotional and psychological meanings. The research is grounded in Conceptual Metaphor Theory proposed by George Lakoff and Mark Johnson, which views metaphor not only as a linguistic device but also as a cognitive tool for understanding abstract experiences. The objectives of this study are to identify the types of metaphors used in the song lyrics and to interpret their meanings within the context of the album. This research employs a descriptive qualitative method, with song lyrics from nine selected songs in the Mantra Mantra album as the primary data. The data were collected through close reading and analyzed using textual analysis. The metaphors were classified into three types: structural, orientational, and ontological metaphors, followed by interpretation based on their contextual meanings. The findings reveal that all three types of metaphors are present in the lyrics, with ontological metaphors appearing most frequently. These metaphors conceptualize abstract experiences such as anxiety, love, memory, identity, and self-healing through concrete domains like physical objects, movement, space, and human actions. Furthermore, the metaphors form consistent conceptual patterns, such as emotions as physical entities, life as a journey, and self-development as a process of struggle. The study also finds that metaphors in the album carry critical meanings, challenging modern societal values such as productivity pressure, social expectations, and the measurement of success through numerical achievement. In conclusion, metaphors in Mantra Mantra function not only as aesthetic elements but also as cognitive and critical tools that shape human understanding of emotional experiences. They enable listeners to interpret complex psychological conditions and reflect on themes of mental health, self-awareness, and personal growth.